Fluconazole versus itraconazole for the prevention of fungal infections in haemato-oncology. Issue 5 (1st May 1999) - Huijgens, P C; Simoons-Smit, A M; van Loenen, A C; Prooy, E; van Tinteren, H; Ossenkoppele, G J; Jonkhoff, A R
Abstract : AIMS: To compare the efficacy of and tolerance to oral fluconazole and intraconazole in preventing fungal infection in neutropenic patients with haematological malignancies. PATIENTS: 213 consecutive, afebrile adult patients treated with or without autologous stem cell transplantation for haematological malignancies. METHODS: A randomised, double blind, single centre study. Patients were randomly assigned to receive fluconazole 50 mg or itraconazole 100 mg, both twice daily in identical capsules. An intention to treat analysis was performed on 202 patients, 101 in each group. RESULTS: Microbiologically documented systemic fungal infections occurred in four patients in each group. Clinical fungal infection was thought to be present in seven recipients of fluconazole and four of itraconazole. In all 202 patients, 29 proceeded to intravenous amphotericin (amphotericin B), 16 in the fluconazole group and 13 in the itraconazole group. Superficial fungal infection was seen only in three non-compliant patients in the fluconazole group. All these infections were oral. No major differences were noted in the isolates of fungi in mouth washes and fecal samples. Overall mortality was 8.9% (18 deaths; seven in the fluconazole group, 11 in the itraconazole group). Mortality from microbiologically and clinically documented fungal infection was 4.5% (nine deaths; three in the fluconazole group, six in the itraconazole group). Median time to suspected or proven fungal infection was 16 days in both groups. None of these comparisons reached statistical significance (p < 0.05). No major clinical toxicity was noted and compliance was excellent. CONCLUSIONS: In neutropenic patients treated for haematological malignancies with or without autologous stem cell transplantation, fluconazole and itraconazole in low doses result in a similar low frequency of fungal disease. Fluconazole may be the preferable drug because of the smaller number of capsules and lack of need for timing relative to meals.